Identification and validation of the common pathogenesis and hub biomarkers in Hirschsprung disease complicated with Crohn’s disease - Wang, Jing; Li, Zejian; Xiao, Jun; Wu, Luyao; Chen, Ke; Zhu, Tianqi; Feng, Chenzhao; Zhuansun, Didi; Meng, Xinyao; Feng, Jiexiong (Frontiers in Immunology, 2022)
Background: Although increasing evidence has supported that Hirschsprung disease (HSCR) is the risk factor for children developing Crohn’s disease (CD), the common mechanism of its co-occurrence remains unknown. The purpose of this study is to further explore the underlying mechanism and biomarkers for the co-occurrence of HSCR and CD. Methods: The Gene Expression Omnibus (GEO) database was used to obtain gene expression profiles for CD (GSE98502) and HSCR (GSE95095). Following the identification of the shared differentially expressed genes (DEGs) of CD and HSCR, functional annotation, protein-protein interaction (PPI) network creation, and module assembly were performed to discover hub genes. RT-qPCR was performed to validate the expression of the hub genes in HSCR samples. The receiver operating characteristic curve (ROC) were utilized to assess the accuracy of the hub genes as biomarkers in predicting CD in both training dataset and test dataset. Results: A total of 103 common DEGs (50 downregulated genes and 53 upregulated genes) were chosen for further investigation. The importance of chemokines and cytokines in these two disorders is highlighted by functional analysis. MCODE plug identified three important modules, which functionally enriched in immune system process. Finally, 9 hub genes were identified using cytoHubba, including IL1B, IL10, CXCL10, ICAM1, EGR1, FCGR3A, S100A12, S100A9, FPR1. The nine hub genes were mainly enriched in immune- and inflammation-related pathways. External data profiles and RT-qPCR confirmed the expression of the nine hub genes in HSCR and CD. ROC analysis revealed that the nine hub genes had a strong diagnostic value. Conclusion: Our study reveals the common pathogenesis of HSCR and CD. These hub genes and diagnostic model may provide novel insight for diagnosis and treatment of the HSCR complicated with CD.